2006
DOI: 10.1080/10570310500506953
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Media and Social Justice Movements: The Development of a Resistance Performance Paradigm of Audience Analysis

Abstract: This study examined the performances of social justice activists who were audiences of alternative media-media that are defined by their resistance to social and corporate power structures. Contemporary performance-oriented audience paradigms do not take into account power and ideology, which are integral to the content of alternative media. Through interviews with 27 social justice activists and qualitative analysis of the alternative media content that they used to gain information about social justice and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 33 publications
(35 reference statements)
0
41
0
3
Order By: Relevance
“…For instance, through qualitative content analysis of alternative media texts used by activists in a town called Mystical City, I searched for examples in which the producers of the texts described so-called enemies along with the alleged problems that they posed to society. The results of the analysis demonstrated that the alternative media used by those activists entailed overarching themes of 'human rights' and 'democracy'; for example, corporations (such as Enron) stood as enemies who threatened both human rights and democracy through their actions and their contributions to political candidates (Atkinson, 2005;Atkinson, 2010;Atkinson and Dougherty, 2006). My past RP research demonstrated the backdrop against which the Communicative Resistance was carried out in local communities.…”
Section: Resistance Performance: An Examination Of Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, through qualitative content analysis of alternative media texts used by activists in a town called Mystical City, I searched for examples in which the producers of the texts described so-called enemies along with the alleged problems that they posed to society. The results of the analysis demonstrated that the alternative media used by those activists entailed overarching themes of 'human rights' and 'democracy'; for example, corporations (such as Enron) stood as enemies who threatened both human rights and democracy through their actions and their contributions to political candidates (Atkinson, 2005;Atkinson, 2010;Atkinson and Dougherty, 2006). My past RP research demonstrated the backdrop against which the Communicative Resistance was carried out in local communities.…”
Section: Resistance Performance: An Examination Of Contentmentioning
confidence: 99%
“…RP has emerged from those efforts (Atkinson, 2005;Atkinson and Dougherty, 2006). The concept of RP focuses on the role of alternative media in the construction and co-performance of resistance against dominant power structures in local level communities.…”
Section: Past Challenges For Alternative Media Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Bolin (2012) suggests that ordinary people are capable of creating their own meaning of media content and of using it for a variety of purposes. Because the media tends to focus on a certain group of people, marginalising the rest, the marginalised people engaging in the news media often emerge as social activists, illustrating the performance of resistance to the rational media (Atkinson and Dougherty, 2006). Such resistances initiated by activists -who use alternative media to express their views -often lead to social justice movementsmovements that work to advocate for people who are economically, socially, or politically marginalised in their own communities and global societies (Frey 1998, cited in Atkinson and Dougherty, 2006).…”
Section: Ordinary People As Content Creatorsmentioning
confidence: 99%
“…Such research has demonstrated how activists pass information framed within nebulous narratives characterized by themes such as ''be the media'' (Pickard, 2006a) or ''democracy'' (Atkinson & Dougherty, 2006) through the use of media produced exclusively within their networks. The narratives appeal to a range of activists, who can then merge together and construct short-term protest communities when those broad themes seem to be threatened (e.g., Best, 2005).…”
mentioning
confidence: 99%